Experimental Study on the Principle of Oxygenation and Oxygenation Performance of Surface Blade Aerator - Pu Xing; Chen Yu; Kangkang Li; Hui Wu (Advances in Materials Science and Engineering)
In this article, the principle of aeration of aerator is analyzed through CFD simulation analysis and high-speed camera observation of aerator blades. Firstly, the flow field of oxidation ditch under the influence of a new curved blade aerator is simulated and analyzed. Then, the oxygenation performance of aerator under different operating parameters, that is different immersion depth and speed, is experimentally studied, and the structural optimization design of blade is carried out. Finally, the best parameters affecting oxygenation dynamic efficiency are obtained by fitting the experimental data, which provides a reference for the further optimization design of the aerator.